2021
DOI: 10.1111/cogs.12947
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Signal in Perceptual Tuning of Speech: Bottom Up Versus Top‐Down Information

Abstract: Cognitive systems face a tension between stability and plasticity. The maintenance of long‐term representations that reflect the global regularities of the environment is often at odds with pressure to flexibly adjust to short‐term input regularities that may deviate from the norm. This tension is abundantly clear in speech communication when talkers with accents or dialects produce input that deviates from a listener's language community norms. Prior research demonstrates that when bottom‐up acoustic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 47 publications
(112 reference statements)
2
17
0
Order By: Relevance
“…Two prior studies are especially interesting in this regard. In a dimension-based statistical learning paradigm like the one used here, Zhang et al (2021) examined the impact of speech category activation on perceptual reweighting through top–down lexical knowledge. In their study, listeners identified nonminimal-pair word-nonword pairs, like beef-peef and beace-peace .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two prior studies are especially interesting in this regard. In a dimension-based statistical learning paradigm like the one used here, Zhang et al (2021) examined the impact of speech category activation on perceptual reweighting through top–down lexical knowledge. In their study, listeners identified nonminimal-pair word-nonword pairs, like beef-peef and beace-peace .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, upon encountering a block of trials that conveys an “accent” in which the F0 × VOT relationship is reversed from English norms, listeners rapidly down-weight reliance on F0 such that it no longer reliably signals /b/ versus /p/. These results, replicated many times and apparent for vowel as well as consonant categorization, demonstrate the flexibility of the mapping from acoustics to speech categories upon encountering short-term regularities that depart from the norm (Idemaru & Holt, 2011, 2014, 2020; Lehet & Holt, 2017, 2020; Liu & Holt, 2015; Schertz et al, 2016; Zhang et al, 2021; Zhang & Holt, 2018).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Though there remain many open questions even for adaptive plasticity across segmental speech categorization, in general patterns of generalization seem to be consistent with an account that category activation drives reweighting (Idemaru & Holt, 2011; Zhang et al, 2021; Wu & Holt, under review; Wu, 2020) and the mechanism for this may involve supervised error-driven learning (Guediche et al, 2014; Wu, 2000) or reinforcement learning (Harmon et al, 2019). To the extent that short-term input regularities across acoustic dimensions are effective in activating a suprasegmental category even as they deviate from long-term expectations of correlations among input dimensions, we would anticipate re-weighting and modest generalization.…”
Section: Discussionmentioning
confidence: 58%
“…This observation suggests that, in the initial stages of the communicative interaction, oxytocin increased exploration of different adjustments to the two presumed addressees, followed by a convergence of the communicative adjustments directed to those addressees. It is known that communicators spontaneously integrate prior knowledge about their interlocutor with the ongoing communicative experience (Brennan et al, 2010;Clark & Krych, 2004;Hawkins et al, 2021;Kuhlen et al, 2012;Zhang et al, 2021). The behavioral finding of this study illustrates how oxytocin enhances that integration and facilitates the implementation of the Gricean Maxim of Quantity, namely producing utterances that convey no more information than necessary (Blokpoel et al, 2012;Brennan & Clark, 1996;de Ruiter et al, 2010;Garrod & Anderson, 1987;Grice, 1975;Levinson, 2000;Liu et al, 2019;Yoon & Brown-Schmidt, 2018).…”
Section: Oxytocin Modulates Dynamics Of Recipient Designmentioning
confidence: 60%